(untitled) (Research, Society and Development, 2022)
Objective: To analyze the main factors associated with the occurrence of postpartum depression. Methodology: A systematic review of the literature based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method, carried out in the electronic databases Pubmed, Scielo, Scopus and Web of Science, using the following descriptors: “postpartum depression”, “postnatal depression”, “maternity blues”, “puerperal depressive symptom”, “after birth depression”, “risk factors” and “dangerous factors”. Full articles, available in Portuguese, English or Spanish, published between 2016 and 2021 were included. Results: 12 articles made up the final sample of this study. It was found that five axes of factors associated with postpartum depression were identified: sociodemographic, psychological, social, hormonal and obstetric. Most of these factors are interrelated and associated with the woman’s lifestyle, especially social factors such as low social and family support, marital conflict and dissatisfaction, and exposure to intimate partner violence during pregnancy. The most frequently listed risk factors were physical, ranging from a history of premenstrual syndrome to obstetric issues such as multiparity, morbidity during pregnancy, unplanned pregnancy, history of miscarriage, cesarean delivery, preeclampsia, placenta previa, placental abruption, premature delivery, hyperemesis gravidarum, gestational hypertension and gestational diabetes. Conclusion: It was found that the factors associated with postpartum depression can be sociodemographic, psychological, social, hormonal and obstetric. Therefore, prevention programs for this clinical condition, such as psychological prenatal care, need to focus on the interpersonal relationships of the individuals involved, in addition to social factors and lifestyle and the physical health conditions of these women.